Akibat Hukum Pemalsuan Dokumen Perkawinan Campuran di Indonesia (Studi Kasus Jessica Iskandar dan Ludwig Franz Willibald) - Hidayat, Rizza Nafaani; Susanti, Rahtami; Kartini, Ika Ariani (UMPurwokerto Law Review, 2024)
Abstract Falsification of letters / documents can be interpreted as an act that has the aim of completing, creating an object which is not original in nature or making an object lose its validity. Mixed Marriage is regulated in Article 57 of Law Number 16 of 2019 concerning amandments to Law Number 1 of 1974 concerning Marriage. In order for the marriage to be registered, the conditions, such as a marriage document, must be fulfilled. If there is falsification of mixed marriage documents, the marriage can be canceled. The cancellation of mixed marriages has an impact on the legal status of the marriage and the parties involved. Cases of falsification of mixed marriage documents that have occurred in Indonesia that ever done by artist Jessica Iskandar who falsified her mixed marriage documents. The purpose of this study was to determine the legal consequences of falsifying mixed marriage documents in Indonesia (Case study of Jessica Iskandar and Ludwig Franz Willibald) and the legal protection of children who has been born. The research method used is juridical normative, namely through literature study that examines mainly secondary data in the form of statutory regulations, agreements or contracts, other legal documents, research results, assessment results, and other references. Â Keywords: Documents Falsification, Mixed Marriage Â Abstrak Pemalsuan surat/dokumen dapat diartikan sebagai suatu perbuatan yang mempunyai tujuan untuk meniru, menciptakan suatu benda yang sifatnya tidak asli lagi atau membuat suatu benda kehilangan keabsahannya. Perkawinan Campuran diatur dalam Pasal 57 Undang-Undang Nomor 16 Tahun 2019 tentang perubahan atas Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan. Agar perkawinan tersebut dapat dilakukan pencatatan maka syarat-syaratnya seperti dokumen perkawinan harus dipenuhi. Jika terdapat pemalsuan dokumen perkawinan campuran maka perkawinan tersebut dapat dibatalkan. Pembatalan perkawinan campuran berdampak pada status hukum perkawinan tersebut dan pihak-pihak yang terkait. Kasus pemalsuan dokumen perkawinan campuran yang pernah terjadi di Indonesia adalah yang pernah dilakukan oleh artis Jessica Iskandar yang memalsukan dokumen perkawinan campurannya. Tujuan dari penelitian ini adalah mengetahui akibat hukum pemalsuan dokumen perkawinan campuran di Indonesia (Studi kasus Jessica Iskandar dan Ludwig Franz Willibald) dan perlindungan hukum terhadap anak yang dilahirkan. Metode penelitian yang digunakan adalah yuridis normatif yaitu melalui studi pustaka yang menelaah terutama data sekunder berupa Peraturan Perundang-undangan, perjanjian atau kontrak, dokumen hukum lainnya, hasil penelitian, hasil pengkajian, serta referensi lainnya. Â Kata kunci: Pemalsuan Dokumen, Perkawinan Campuran